Phosphate scarcity governs methane production in the global open ocean - Shengyu Wang; Hairong Xu; Thomas S. Weber (Proceedings of the National Academy of Sciences, 2026)
The observed supersaturation of methane (CH 4 ) in open-ocean surface waters implies widespread CH 4 production within the well-oxygenated mixed layer, driving emissions of this potent greenhouse gas to the atmosphere. The dominant CH 4 production pathway that explains this phenomenon remains poorly understood, although candidates include production during photosynthesis, zooplankton metabolism, and dissolved organic matter cycling. Here, we construct a data-assimilating model of the open-ocean CH 4 cycle to test which hypothesized mechanism is most consistent with the observed global CH 4 distribution. We find that only linking methane production to phosphate (PO 4 ) scarcity can explain the observed supersaturation pattern, which is highest in subtropical gyres where PO 4 is in short supply. These findings suggest that CH 4 release during PO 4 -limited cleavage of the organic compound methylphosphonate is the dominant production pathway in the open ocean. Because this process is confined to the stratified low latitude surface, it is uniquely suited to efficiently emit the CH 4 it produces to the atmosphere (>90%), before the CH 4 mixes to depth and undergoes oxidation (<10%). As predicted future ocean warming and stratification exacerbates PO 4 scarcity over coming centuries, our model predicts that oxic CH 4 production and the resulting CH 4 emissions will increase up to twofold, contributing to a suite of positive feedback between climate warming and natural greenhouse gas sources.